Trade Union Regional Conference on the Beveridge Report : abridged report - Trades Union Congress
1943-01-16 1943 1940s 7 pages 5 General Workers' Delegate: "What is going to happen to goods made at trading centres ? Will the goods be sold cheaper to the detriment of the producer?" Mr. Corby: "That happens now under some voluntary schemes, but under the Beveridge Scheme they would be distributed according to the will of Parliament." Another delegate urged that if the Beveridge Report was not adopted before hostilities ceased, it would be shelved. Question : "Would the T.U.C. recognise administration by Trade Unions for their members ?" Mr. Corby: "Industrial Societies are framing Friendly Societies for their branch interests at the expense of health insurance. I want to see it discontinued. With this exception, then, the T.U.C. does want the Trade Unions to administer. They do not want the Friendly Societies to administer. They want the Trade Unions to administer health insurance on the same lines as unemployment insurance." Mr. Corby continued : "I don't want Industrial Societies to come into this insurance. 7s. 6d. out of every £1 they collect is taken in management expenses." Delegate : "Can you tell me why these four main Forces have been prohibited from discussing the Beveridge Report in view of the fact that the majority of the men who administer approved societies are now serving in H.M. Forces, and their lives are at stake?" Mr. Bussey : "I think the matter has been given the widest publicity, and the action of the War Minister richly deserved the general outcry of the country, which will lead to an alteration of policy in respect to this matter. It is pretty obvious the reason the action was taken by the Minister was no implication so far as the Report is concerned." Woodworkers' delegate asked whether it was possible for the Beveridge Report to be held up by the vested interests as long as we were in a minority in the House of Commons. Mr. Corby replied that he believed that the present Parliament dare not hold it up, as the Report had received such public support not only in this country, but abroad, and further, that the Government had allowed the B.B.C. to broadcast it. By doing this the Government had put something round its own neck which it could not easily get off. I am afraid about killing it by asking for more than is in it. (Applause.) 292/150.5/5/206